Last Glacial loess in Europe: luminescence database and chronology of deposition - Bosq, Mathieu; Kreutzer, Sebastian; Bertran, Pascal; Lanos, Philippe; Dufresne, Philippe; Schmidt, Christoph (Earth system science data, 2023)
During the Last Glacial Period, the climate shift to cold conditions associated with changes in atmospheric circulation and vegetation cover resulted in the development of large aeolian systems in Europe. On a regional scale, many factors may have influenced dust dynamics, such as the latitudinal difference between the various aeolian systems and the variability of the sources of wind-transported particles. Therefore, the assumption that the timing of aeolian deposition is strictly synchronous in Europe does not seem to be the most plausible hypothesis and needs to be evaluated. To test this assumption, the chronology of loess deposition in different European regions was investigated by studying 93 luminescence-dated loess-palaeosol sequences with their data recalculated and compiled in a single comma separated values (*.csv) file: the ChronoLoess database. Our study shows that the two major aeolian systems, the Northern European Loess Belt (NELB) on the one hand and the systems associated with the rivers draining the Alpine Ice Sheet on the other hand, developed asynchronously. The significant deposition started at about 32 kyr b2k for the NELB vs. 42 kyr b2k for the perialpine loess and peaked about 2 millennia later for the former (21.8 vs. 23.9 kyr b2k, respectively). This shift resulted mainly from the time lag between the maxima of the Alpine and Fennoscandian ice sheets, which acted as the primary sources of fine-grained particles through glacial abrasion. The major geomorphic changes that resulted from the development and decay of the Fennoscandian and British-Irish ice sheets also played an important role. Particularly, ice sheet coalescence during the Last Glacial Maximum (LGM) diverted meltwater fluxes through the Channel River and provided vast amounts of glacial particles available for deflation in the western NELB. The period during which the maximum mass accumulation rate was reached for each loess-palaeosol sequence is relatively homogeneous in the NELB and ranges from 30 to 19 kyr b2k, whereas it is more scattered in the perialpine systems (>60 to 14 kyr b2k). This probably resulted from a combination of factors, including the asynchrony of maximum valley glacier advances and local geomorphic factors. The ChronoLoess database is available at https://doi.org/10.5281/zenodo.7728616 (Bosq et al., 2023).
Gesehen am 17.01.2025